Pelatihan Pembukuan Sederhana pada UMKM Bidang Ritel di Desa Cileungsi Kecamatan Cileungsi Bogor - Nurhasan, Nurhasan; Septia B, Rico; Baharsyah, Syamsudin (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Financial bookkeeping will produce a more informative financial report in order to provide complete information to third parties. However, in practice, MSME owners are unable to provide financial information because there are no financial reports. In line with the above, the quality of MSME existence must be improved starting from operational activities to how to practice simple bookkeeping with the aim of orderly bookkeeping and presentation of financial reports. The purpose of this service activity is to deepen knowledge and understanding regarding simple bookkeeping in business activities and improve skills in making simple bookkeeping and applying it regularly in business activities. In this service activity, participants are given material to training and assistance related to simple bookkeeping. This activity was attended by 20 retail business actors around the Cileungsi Village area. Based on the Community Service activities that have been carried out, it is concluded that this Community Service activity deepens the understanding and knowledge of retail business actors regarding simple bookkeeping in business activities. Business actors gain knowledge and skills regarding new insights in running their business through simple bookkeeping or financial records that are easy to apply. After this activity, business actors can implement even better bookkeeping and recording as a financial recording system in business activities.